2002
DOI: 10.1074/jbc.m207326200
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of p38 Mitogen-activated Protein Kinase in Contact Hypersensitivity

Abstract: The present study was designed to elucidate the role of p38 mitogen-activated protein kinase (p38) in the pathogenesis of inflammation, using a mouse contact hypersensitivity (CHS) model induced by 2,4-dinitro-1-fluorobenzene (DNFB).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 46 publications
4
49
0
Order By: Relevance
“…Among them, p38␣ and -␤ are expressed relatively ubiquitously, as shown by Northern blot analysis of adult tissues (4). Although targeted disruption of the p38␣ gene results in homozygous embryonic lethality because of defects in erythropoiesis and placental organogenesis (5,6), the p38␣ ϩ/Ϫ mouse is a useful tool for analyzing the in vivo role of p38 in disease models (7)(8)(9).…”
Section: Mice Platelets Of P38␣mentioning
confidence: 99%
“…Among them, p38␣ and -␤ are expressed relatively ubiquitously, as shown by Northern blot analysis of adult tissues (4). Although targeted disruption of the p38␣ gene results in homozygous embryonic lethality because of defects in erythropoiesis and placental organogenesis (5,6), the p38␣ ϩ/Ϫ mouse is a useful tool for analyzing the in vivo role of p38 in disease models (7)(8)(9).…”
Section: Mice Platelets Of P38␣mentioning
confidence: 99%
“…p38 MAPK are enzymes that play an important role in the signal transduction of TLR (Mehrotra et al, 2007). In mice treated with the specific p38 MAPK inhibitor SB202190 the ear swelling in response to DNFB was impaired (Takanami-Ohnishi et al, 2002). Further evidence for the importance of p38 MAPK was found in in vitro studies.…”
Section: The Role Of Tlrs In Skin Sensitizationmentioning
confidence: 62%
“…Meanwhile, in the mesenteric lymph nodes, where pre-matured T cells expand and mature into cytotoxic T cells, donor-derived CD8 + and CD4 + lymphocytes are fewer in p38a +/--grafted mice. Several studies have reported that activated p38 up-regulates the expression of several cytokines, such as IL-12p40, IL-18, and IL-4 [16,17,27], and plays essential roles in T cell proliferation in vitro and in vivo [18][19][20]. The induction of Th1-dominant cytokines, such as IL-12p40 and IL-18, was suppressed in the MLNL of p38a +/--grafted mice, which may be one of the reasons why fewer lymphocytes infiltrated into the MLNL.…”
Section: Discussionmentioning
confidence: 99%
“…The B6 mice that carry the GFP transgene (B6-GFP mice) were a gift from Dr. Masaru Okabe (Osaka University, Osaka, Japan) [42]. Mice heterozygous for targeted disruption of the p38a gene in the B6 background (p38a +/-) were maintained in RIKEN BioResource Center (Tsukuba, Japan) [13,27]. GFP-WT and GFP-p38a +/-mice were generated as donor mice by mating B6-GFP and B6-p38a +/-mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation